2020
DOI: 10.29040/ijebar.v4i03.1282
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Customer Trust and Company Image on Customer Satisfaction and Customer Loyalty in Indonesia Classification Bureau in Samarinda

Abstract: This study aims to determine the effect of customer trust and company image on customer satisfaction and customer loyalty at the Indonesian Classification Bureau. The population in this study were customers of PT BKI with a total of 95 respondents. The method of data collection is done by giving a list of questions or questionnaires to respondents who are customers at PT BKI, where the questionnaire is distributed to these customers. This study uses a data analysis tool that is partial Least Square (PLS), then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 7 publications
3
10
1
4
Order By: Relevance
“…High service quality can be achieved by identifying problems in service and defining measures for service performances and outcomes as well as level of customer satisfaction (Suciptawati et al, 2019), Service quality is an abstract conception and is like to be understood because the quality of service has intangible characteristics (intangibility), varied (variability), nondurable (perishability), and production and consumption of services occur simultaneously (inseparability) (Putra & Amrial, 2021), the results showed that the quality of service has a positive and significant influence on customer satisfaction, this is in line with the research of (Maharsi et al, 2021), (Utomo et al, 2022) that customer satisfaction is influenced by the high or low quality of service. Services are well able to determine the satisfaction of consumers is the quality of services (Mahsyar & Surapati, 2020). Service quality has a positive impact on customer satisfaction.…”
Section: The Effect Of Service Quality On Customer Satisfactionmentioning
confidence: 99%
“…High service quality can be achieved by identifying problems in service and defining measures for service performances and outcomes as well as level of customer satisfaction (Suciptawati et al, 2019), Service quality is an abstract conception and is like to be understood because the quality of service has intangible characteristics (intangibility), varied (variability), nondurable (perishability), and production and consumption of services occur simultaneously (inseparability) (Putra & Amrial, 2021), the results showed that the quality of service has a positive and significant influence on customer satisfaction, this is in line with the research of (Maharsi et al, 2021), (Utomo et al, 2022) that customer satisfaction is influenced by the high or low quality of service. Services are well able to determine the satisfaction of consumers is the quality of services (Mahsyar & Surapati, 2020). Service quality has a positive impact on customer satisfaction.…”
Section: The Effect Of Service Quality On Customer Satisfactionmentioning
confidence: 99%
“…Sikap baik konsumen setelah konsumen produk atau jasa menggambarkan kepercayaan (Mahsyar et al, 2020). Perilaku menggunakan produk atau layanan sebelumnya menunjukkan bahwa konsumen menaruh rasa percaya (Komalasari et al, 2021).…”
Section: Kepercayaanunclassified
“…Mengabaikan kualitas layanan dapat berdampak pada ketidakpuasan konsumen terhadap bisnis/organisasi. Dengan demikian, kualitas pelayanan merupakan atribut yang berperan penting dalam memasarkan produk atau jasa yang ditawarkan (Mahsyar & Surapati, 2020). Harga tidak hanya berkaitan dengan kualitas layanan, tetapi juga merupakan salah satu bentuk strategi pemasaran.…”
Section: Pendahuluanunclassified